Identification and instructional strategies in the management of giftedness in the classroom: the role of teachers (2019)
This paper reviewed the strategies teachers could use in identifying, instructing and managing giftedness of students in the classroom. In the paper, the meaning and concept of giftedness was looked into after which the authors discussed the characteristics common to gifted children. The three broad characteristics examined are physical characteristics, Educational/Intellectual Characteristics, Social and Emotional Characteristics. The formal and informal ways of identifying gifted children were examined. The paper further discussed the role a teacher can play in managing giftedness in the Nigerian educational setting. Finally, conclusion was drawn and recommendations made. It was recommended that teachers should be flexible, open, have strong communication skills as well as positive sense of self.